The Use of Educational Chemistry Resources for Students in Academic Daytime Secondary Schools of San Jose School Districts 09 and 11, Costa Rica - Chacón-Ramírez, Nancy (2016)
This article presents the results of an investigation conducted to identify which didactic materials teachers have to teach chemistry in two academic secondary schools of the school districts 09 and 11. This research responds to a study complemented with the qualitative approach, given the nature of categories of analysis and data collected. The techniques and instruments used were questionnaires, interviews and descriptive observation. The population studied consisted of two teachers and 130 students. The main results of the investigation show that one of the schools studied has a wide range of resources to carry out experimental activities with their students, while the other academic school has neither laboratory nor proper equipment for such activities. Part of the student population interviewed believes that the lessons of chemistry are interesting, but others believe otherwise, since they consider them as boring and less dynamic. It can be proposed to work in the students’ construction of knowledge so that they would be interested in chemistry and, from work and interest, they could construct their knowledge significantly.